Parental opposition to comprehensive sexuality education in Australia: associations with religiosity and school sector - Hendriks, Jacqueline; Francis, Neil; Saltis, Hanna; Marson, Katrina; Walsh, Jenny; Lawton, Natasha; Burns, Sharyn (Frontiers in Psychology, 2024)
Purpose: To empirically examine associations between parental opposition towards comprehensive sexuality education (CSE) and religiosity. Methods: A nationally representative survey of Australian parents (N=2,418) examined opposition towards 40 CSE topics, by parental religiosity and secular/religious school sector. Results: Whilst opposition to most CSE topics correlated positively with religiosity, even amongst very religious parents, disapproval was minimal (2.8%-31.2%; or 9.0%-+20.2% netted against non-religious parents). Parents with children enrolled in a Catholic school were less likely than secularschool parents to oppose CSE. Those with children at other-faith-schools were more likely to oppose CSE, but again disapproval was minimal (1.2%-21.9%; or 1.3%-9.4% netted against secular-school parents). Discussion: Only small minorities of very religious parents and parents with children in religious schools opposed the teaching of various CSE topics. Decision-makers should therefore be cautious about assuming that CSE delivery is not widely supported by particular families.